(untitled) (مجلة إحالات, 2026)
The learning and teaching processes had marked a remarkable paradigm shift from the past to the present era. Interestingly, the recent globalized movement towards a digital shift in education necessitates a completely rethinking pedagogy; that aims to face up complex educational challenges. (Kearne, 2020) One of the challenges is how to foster learners’ digital literacy. Remarkably, the project-based approach to teaching has been designed to ensure that learners take responsibility for their learning as a child-centered method. Importantly, it emphasizes a variety of methods including active learning, cooperative learning, and inductive learning thus outstanding forerunners of project-based approach are unforgettable theorists such as John Dewey, William Kilpatrick, Kolmos Anette, and others. Project-based learning gained significant popularity and widespread credence as an effective approach. Doubtlessly, the present work is conducted to analyse the role of a project-based approach in enhancing learners’ digital literacy and collaboration.